2022
DOI: 10.1111/evj.13590
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive diode laser–an effective and safe treatment of iris cysts in 46 eyes of 35 horses

Abstract: Background: Iris cysts in horses are often asymptomatic and noticed incidentally.However, cysts can cause local corneal oedema and erratic behaviour like shying, decreased performance and head-shaking.Objectives: To describe the use of diode laser as a noninvasive treatment option for iris cysts in the horse and to document factors influencing its efficacy, associated complications, long-term outcome and rate of recurrence. Study design: Retrospective case series. Methods: Case records of horses treated for ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 27 publications
3
10
0
Order By: Relevance
“…Ultrasound is reported to rarely be required as iris cysts have a very characteristic appearance (Gilger et al., 2022 ); however, Stas et al. ( 2023 ) reported that ultrasound prior to treatment aided in evaluating the number of cysts and their appearance including the size, architecture and wall thickness. They found this to be useful information to determine treatment success rates and surgical planning when using a diode laser.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Ultrasound is reported to rarely be required as iris cysts have a very characteristic appearance (Gilger et al., 2022 ); however, Stas et al. ( 2023 ) reported that ultrasound prior to treatment aided in evaluating the number of cysts and their appearance including the size, architecture and wall thickness. They found this to be useful information to determine treatment success rates and surgical planning when using a diode laser.…”
Section: Discussionmentioning
confidence: 99%
“…Equine primary iris cysts are smooth, often focal swellings that are darker than the iris and usually attached to the pupillary margin, arising from the inner non‐pigmented ciliary body epithelium (Dziezyc et al., 1990 ; Shields et al., 1984 ). They are often an incidental finding in the horse but have been reported to cause behavioural changes including spooking, poor performance often associated with jumping and headshaking (Berger et al., 2008 ; Stas et al., 2023 ). Occasionally, they have been reported to contact the corneal endothelium, leading to oedema formation with recurrent corneal ulceration (Byam‐Cook & Knottenbelt, 2007 ; Stas et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations